2018
DOI: 10.1002/ejic.201701446
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Tuned C–H Bond Activation/Arylation of 2‐Arylpyridines over Pyridine‐Based N,O/N,N Ligated Ruthenium–Arene Complexes

Abstract: Water-soluble ruthenium(II)-arene complexes [(η 6arene)Ru(κ 2 -L)] n+ (n = 0, 1) ([Ru]-1-[Ru]-10) containing pyridine-based bischelating N,O/N,N donor ligands (L1-L5) are synthesized and employed for the catalytic C-H bond activation/ arylation of a wide range of 2-phenylpyridines and aryl halides in water, affording the corresponding mono-and biarylated products. Exploring the reactivity of the synthesized complexes, our investigations, including time-dependent 1 H NMR spectroscopic studies with ruthenium-are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…Further, it was also evident from the DFT calculations that the species 2A‐I having acetyl group in the close proximity of ortho proton of 2‐phenylpyridine was stable by 2.7 kcal/mol than the species 2A‐II having carboxylate group in that place. These results are in concurrence with earlier reports,, , suggesting that presumably the acetyl group was involved in the C‐H bond activation of 2‐phenylpyridine (Figure S5). Further, upon replacing the ligand L1 with 2,5‐hexanedione ( L8 ), free energy calculations revealed that the C‐H activation reaction was highly unfavorable in the presence of L8 (Δ G = 30.7 kcal/mol) (Table S2).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Further, it was also evident from the DFT calculations that the species 2A‐I having acetyl group in the close proximity of ortho proton of 2‐phenylpyridine was stable by 2.7 kcal/mol than the species 2A‐II having carboxylate group in that place. These results are in concurrence with earlier reports,, , suggesting that presumably the acetyl group was involved in the C‐H bond activation of 2‐phenylpyridine (Figure S5). Further, upon replacing the ligand L1 with 2,5‐hexanedione ( L8 ), free energy calculations revealed that the C‐H activation reaction was highly unfavorable in the presence of L8 (Δ G = 30.7 kcal/mol) (Table S2).…”
Section: Resultssupporting
confidence: 93%
“…The above findings inferred that the facile coordination of the ligand L1 in a bidentate manner with the ruthenium center via acetyl and carboxylate‐O – groups, as also evidenced by the presence of levulinate coordinated arene‐Ru species ( [Ru]‐A ) (m/z = 351, [M] – Cl) during mass studies, is presumably responsible for the observed accelerated catalytic activity. In this context, previous studies also revealed that analogous bis‐chelating ligands may display coordination/de‐coordination behavior during the catalytic reaction and hence significantly tune the catalytic reactivity (Scheme S2) , , . It is also evident from the literature that the enhanced catalytic activity in Ru‐picolinate systems was due to the involvement of acetyl group in C‐H deprotonation, while remain coordinated with metal center with strongly coordinating pyridine …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations